Contribution of Japanese Aid to the Development Process of Nepal - Dhakal, Chandra Prasad (International Research Journal of MMC, 2022)
Japan is one of the developed nations of the world. It has provided various supports to the developing and under developed nations. Nepal established a friendship relationship with Japan in 1965. Since the time of friendship establishment, Japan has been playing a major role in the development process of Nepal. Loan assistance, technical supports, and grand assistance are provided by Japan to Nepal. Japanese aid is increasing in trend; however, the sector is changing on the basis of the priority of Nepal government. Japanese aid is basically used in human development and infra structure development. The result of the Japanese aid is effective in grass root level. The priority of the aid has brought positive changes in community. The study followed the mixed method and analyzed the collected data by through qualitative and quantitative research design. Numerical data were projected in table and figure other information mentioned through paragraph description. On the basis of data analysis and discussion, conclusion has been made. The portion of Japanese aid is high and the utilization ofthe aid has brought a positive impact on both human development and infrastructure development in Nepal.